Dynamic Programming-Based Distribution Route Optimization with WinQSB and Field Validation in a Footwear SME - Nadiya Maharani; Fadil Abdullah; Wan Habibi Rahman Barus; Muhammad Alif Ihsan (Politeknik META Industri Cikarang, 2026)
Background Product distribution is a logistics activity that affects the operational efficiency of MSMEs, particularly in the footwear industry in the Cibaduyut area of Bandung. The main problem identified is the lack of standardized distribution routes, resulting in deliveries still being based on drivers’ intuition. This situation leads to inconsistent routes, fuel waste, and inefficient delivery times Purpose This study aims to optimize distribution routes using the Dynamic Programming method, validated with WinQSB, and compared against the Traveling Salesman Problem (TSP) and Dijkstra’s Algorithm. Methodology The methodology employed is an applied quantitative approach using data on distances between distribution points, travel time, fuel consumption, and GPS tracking. Findings The optimization results show a reduction in distribution distance from 35.2 km to 26.8 km and in delivery time from 82 minutes to 61 minutes. Efficiency improvements were 23.86% for distance, 25.61% for time, and 24.26% for fuel costs. Validation using WinQSB and GPS data confirmed that the optimization results align with field conditions. Implications The proposed route optimization provides a practical decision-support tool for MSMEs to improve distribution efficiency, reduce transportation costs, and enhance delivery performance. The findings can assist logistics managers in developing standardized distribution routes and serve as a reference for implementing data-driven distribution planning in small and medium-sized manufacturing enterprises. Originality This study contributes by integrating Dynamic Programming with WinQSB validation and GPS-based field verification to optimize distribution routes for footwear MSMEs. Unlike previous studies that primarily relied on theoretical optimization or simulation, this research demonstrates the practical applicability of the proposed approach in a real distribution network while benchmarking its performance against the Traveling Salesman Problem (TSP) and Dijkstra’s Algorithm.